Project Personnel’s Perception onWatershed Development Activities under NationalWatershed Development Projects for Rainfed Area (NWDPRA) - Purushottam , S.K. Jha; Baldeo Singh (Indian Journal of Extension Education, 2022)
Project personnel under NationalWatershed Development Projects for Rainfed Area (NWDPRA) were selected to study the perception on relatively important watershed activities and involvement in watershed projects. Themajority (67.0%) of project personnel were Graduate followed byMasters (21.0%) and Doctorate degree (12.0%), indicating that the staff was adequately qualified. It was found that the project personnel perceived conservation and production measures (115) more importantly over socio-economic andmanagement aspects (77) for the success of watershed project. It was further observed that these personnel were notmuch clear to their task in watershed development.The overall 21 activities of their involvement in watershed projects were identified. The involvement of themin socio-economic andmanagement aspects (65) was higher over resource conservation and production measures (47). Than total multiple responses of them were higher (192) under relatively important watershed activities over their involvement in watershed activities (112). Indicates significant gaps between the perceived activities and performed activities under the watershed projects. Further, the responses of project personnel on effectiveness of training in watershed indicated that majority (77.14 %) desired for practical and problem-solving training based on local experiences and training programmes to be organized at the village (55.71%),watershed (31.42%) and district levels (21.12%).